Survey on Financial Market Frictions and DSGE models - Viziniuc, Madalin (International Journal of Economics and Financial Issues, 2015)
This survey reviews the research regarding the general frameworks used for the specification of financial market frictions in Dynamic Stochastic General Equilibrium models. Within the related literature, financial frictions are considered to be the prime candidates for endogenous amplification of small transitory non-financial shocks. The latest financial crisis has changed a number of macroeconomic paradigms and DSGE models were not left untouched. Pre-crisis macroeconomic models neglected the financial markets due to the fact the most economists considered them to function perfectly. As economic events pointed out the contrary, numerous research papers that tackle this problem are available in literature, therefore, this rapidly growth of literature motivates this survey. Keywords: DSGE models; financial market frictions; financial accelerator; collateral constraint; survey JEL Classifications: E21; E22; E32; E44; E59